Effectiveness of Panretinal Photocoagulation Plus Intravitreal Anti-VEGF Treatment Against PRP Alone for Diabetic Retinopathy: A Systematic Review With Meta-Analysis - Zhang, Wuyue; Geng, Jinsong; Sang, Aimin (Frontiers in Endocrinology, 2022)
Objective To compare the efficacy and safety of panretinal photocoagulation (PRP) combined with intravitreal anti-vascular endothelial growth factor (anti-VEGF) against PRP monotherapy for diabetic retinopathy (DR). Methods We searched Pubmed, Cochrane Library, Web of Science, Embase, and Science Direct Register of Controlled Trials from April 2011 to January 2021 to identify the randomized trials that compared the efficacy and safety between PRP combined with intravitreal anti-VEGF and PRP monotherapy for DR. We searched in the following databases between April 2011 and January 2021: Pubmed, Cochrane Library, Web of Science, Embase, and Science Direct without any restriction of countries or article type. The outcome measures were the best-corrected visual acuity (BCVA), neovascularization on the disc (NVD), neovascularization elsewhere (NVE), central macula thickness (CMT), and total retinal volume over time (FAS), and we also observed the adverse events (AEs) between the two groups. Results A total of 351 studies were identified, of which 11 studies were included in this meta-analysis (N = 1,182 eyes). Compared with PRP monotherapy, PRP plus anti-VEGF combination treatment produced a mean reduction in BCVA in units of logMAR of -0.23 [95% CI -0.32, -0.15] or a mean improvement in BCVA in units of letters of 4.99 [95% CI 3.79, 6.19], and also yielded a mean reduction in NVD of -28.41 [95% CI -30.30, -26.52], in NVE of -1.33 [95% CI -1.52, -1.14], in CMT of -1.33 [95% CI -1.52, -1.14], or in total FAS. No significant difference was observed on the risk of AEs as vitreous hemorrhage, elevation in intraocular pressure, and cataract between the two different treatments. Conclusion PRP with anti-VEGF combination treatment can achieve the ideal efficacy on DR by improving BCVA and NV regression, with no potential increased incidence of AEs, which proves that the combination therapy is an efficient therapeutic strategy that could improve the management of patients with DR.